Pregnancy in a previous cesarean section scar: Case report - Morales Bautista, José Luis (2024)
Cesarean section represents a procedure whose frequency has increased over time. As a consequence of this history, a complication of pregnancy is reported, the previous cesarean scar pregnancy (PCBS). Some include it as a type of ectopic pregnancy, most do not as such. This complication represents implantation of the blastocyst in a scar defect, described as isthmocele. ECCP can be of two types. The endogenous or type 1, where the gestational sac grows towards the uterine cavity and therefore the myometrium will be thicker; and the exogenous or type 2, with a growth towards the bladder, where the myometrium is very thinned. The management of this pathology is not standardized. Because of the severe maternal morbidity that can occur, and the still controversial management, we report a clinical case managed surgically at the Hospital Nacional Dos de Mayo.